EFFECT OF DIETARY ELECTROLYTE BALANCE AND ARGININE TO LYSINE RATIOS ON PERFORMANCE, NUTRIENT DIGESTIBILITY, EGG QUALITY AND HATCHING TRAITS OF LAYING HENS UNDER CYCLIC HEAT STRESS - Youssef A. Attia; Nicola Francesco Addeo; Fulvia Bovera; Ahmed A. Abdallah; Rashed A. Alhotan; Mohamed A. Al-Banoby; Abd-ElHamid E. Abd-ElHamid; Asmaa Sh. El-Naggar; Reda M. Zaki (Journal of Animal and Plant Sciences, 2025)
This research sought to study the relationship between dietary electrolyte balance (DEB) and the arginine-to-lysine ratio (Arg/Lys) concerning the sustainability of both productivity and reproductive efficiency in laying hens exposed to cyclic heat stress (CHS). A completely randomized design was used with 245 laying hens and 35 cocks randomly assigned to seven distinct experimental treatments between week 32 and 44 of age. The initial treatment was maintained under thermoneutral conditions with a temperature interval of 22–24 °C, accompanied by a relative humidity (RH) level fluctuating between 45% and 55%. The birds in this group were provided with a basal diet consisting of 180 mEq of DEB and a ratio of 1.25 for arginine to lysine (Arg/Lys), serving as a positive control with a DEB-to-Arg/Lys ratio of 144 (thermoneutral group). The remaining treatments were kept under CHS conditions for three consecutive days a week from Sunday to Tuesday at 38 °C and 55-65 % RH from 11.00 am to 15.00 pm. The birds were fed diets with various concentrations of DEB and an Arg/Lys ratio, organized into the following treatments: 180 mEq and 1.25 (negative control, NC), 250 mEq and 1.25, 320 mEq and 1.25, 180 mEq and 1.37, 250 mEq and 1.37, and 320 mEq and 1. 37, respectively. The CHS treatment administered a dosage of 250 mEq of DEB and a ratio of 1.37 for Arg/Lys (resulting in a DEB/Lys ratio of 182.5), which significantly enhanced egg production percentage (EP%). The digestibility of protein and dry matter (DM) percentages were significantly improved by increasing Arg supplementation from 1.25 to 1.37 in 180 DEB. The diet 1.37 Arg/Lys and 250 DEB could be used to elevate CHS adverse effects, improve the apparent protein digestibility. This suggests that the ideal DEB: Arg/Lys ratio for laying hens exposed to CHS is about 182.5.
Keywords: thermal stress; animal health and production; animal nutrition; amino acid metabolism; egg evaluation